Evaluating Physicochemical Properties of Whey-Chia Seed Edible Films for Biodegradable Packaging - Fahrullah, F.; Noersidiq, A.; Kisworo, D.; Maruddin, F. (Faculty of Animal Science, IPB University, 2024)
The use of whey-chia seed edible films can help reduce environmental pollution while preserving the quality of food products. Films were produced using varying ratios of whey to chia seed (v/w) (whey-chia seed ratio of 1:0.5 (W1), 1:0.75 (W2), and 1:1 (W3)) through a completely randomized design with three treatments and six replications. The results showed significant differences (p<0.01) in elongation, tensile strength, moisture content, solubility, and color properties, except for crude fiber content (p>0.05). As the whey:chia seed ratio increased to 1:1, elongation increased up to 76.77%, while tensile strength decreased to 3.876 MPa, indicating an inverse relationship between these properties. The film with a whey:chia seed ratio of 1:0.5 showed 71.08% elongation but higher tensile strength (4.306 MPa) compared to the W3 treatment. The whey:chia seed ratio of 1:1 chia seed film also had the highest moisture content (49.52%), solubility (53.69%), and fiber content (15.67%). Increasing the ratio of chia seed resulted in a brighter and more transparent appearance. The microstructure of the film was continuous, compact, and homogeneous, without any irregularities such as cracks or air bubbles. The study concluded that chia seeds enhance the physicochemical and mechanical properties of whey-based edible films, with the optimal film produced at a 1:1 whey-chia seed ratio.